2007
DOI: 10.1111/j.1365-2524.2007.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Organisation and features of hospital, intermediate care and social services in English sites with low rates of delayed discharge

Abstract: In recent years, there has been significant concern, and policy activity, in relation to the problem of delayed discharges from hospital. Key elements of policy to tackle delays include new investment, the establishment of the Health and Social Care Change Agent Team, and the implementation of the Community Care (Delayed Discharge) Act 2003. Whilst the problem of delays has been widespread, some authorities have managed to tackle delays successfully. The aim of the qualitative study reported here was to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 11 publications
1
67
0
Order By: Relevance
“…As in previous research [28, 31], participants expressed concerns that frail older people were at risk of deteriorating and acquiring infections during their long stays in acute wards. The current study also highlighted that frail older people were frequently moved between acute wards, an issue that has been raised for several years in England [17, 46, 54, 55] and the US [23]. The formation of a quality relationship between practitioners and frail, older people and their relatives supports positive transition experiences [10] but frequent moves affect relationship-building.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…As in previous research [28, 31], participants expressed concerns that frail older people were at risk of deteriorating and acquiring infections during their long stays in acute wards. The current study also highlighted that frail older people were frequently moved between acute wards, an issue that has been raised for several years in England [17, 46, 54, 55] and the US [23]. The formation of a quality relationship between practitioners and frail, older people and their relatives supports positive transition experiences [10] but frequent moves affect relationship-building.…”
Section: Discussionmentioning
confidence: 76%
“…While the patient sample gave some valuable perspectives of transitions at individual and interpersonal level [36], a limitation of the study is the very small sample. Baumann et al reported problems in recruiting participants from a similar population [46]. The recruitment difficulties confirmed that many frail older people were remaining in acute hospital wards for lengthy periods and illuminated the complexity of these patients, as many were neither well enough, nor had the mental capacity, to be able to participate in an interview.…”
Section: Discussionmentioning
confidence: 99%
“…Among organisational factors of delay, some studies emphasise the role of both hospital and primary care processes [13,14]. Hospital discharge is indeed appropriate when the patient does not exhibit evolving clinical symptoms and is assisted after the acute stage of illness through processes that involve different professionals and both health and social facilities [15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the findings from this local implementation will state something about the broad programme theory ('fines work to reduce delayed discharges') as a general theory of change, thus, a number of transferable lessons can be learned from everybody and for everybody. (Baumann et al, 2007) intending to fill the evidence gap regarding solutions to delays. This research analysed sites performing 'exceptionally well' with regards delayed discharges and it drew general knowledge from their practices.…”
Section: Developing Mechanisms and Outcome Patterns In A Selftransformentioning
confidence: 99%